Testing a hypothesis about the importance of the quality of raw material on technological changes at Abric Romaní (Capellades, Spain): Some considerations using a high-resolution techno-economic perspective (Journal of Lithic Studies, 2016)
Technological changes have been identified in several European Middle Palaeolithic sites. Specifically, the turnover in discoid and Levallois knapping methods has traditionally been explained by raw material constraints that are usually related to foraging areas and mobility strategies of Neanderthal groups. While Levallois production requires high homogeneous blocks, predominant discoid techno-complexes have generally been interpreted as better adapted to the scarcity of high quality raw material, not only for the lowest degree of control in products morphology, but also for their multitask characteristics. Nevertheless, the impact of the quality of raw material has never been systematically studied. Furthermore, technological analyses usually consider the lithic assemblage as a whole and do not dissect assemblages to identify single events, which are units that are needed to interpret relationships between technological organisation, human mobility, economic strategies, and settlement patterns. Here, we present an application of technological analysis with a high-resolution approach to investigate, in detail, how raw material quality affected production and how Neanderthals managed the low quality of Sant Martí de Tous chert within Levallois and discoid concepts. We used Raw Material Units and refits as units of analysis with a diacritical approach. The results suggested that the Levallois organisation of the reduction sequence in layer O included a phase of selection of the block and its systematic cutting-down, as well as quite standardised productive procedures and a high fragmentation of the productive sequence within the landscape. In layer M discoid sequences showed a high internal variability as a response to raw material constraints, and most of the production was usually manufactured at the site. Data implied that factors others than the quality of raw material determined the technological turnover at Abric Romaní, suggesting that social organisation and settlement patterns have most probably played a more significant role than foraging area.